THE GEOPOLITICAL COMPONENTS OF UKRAINIAN CRISIS - Сутула, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article is devoted to the main points of the geopolitical characteristics of Ukrainian crisisregarding throught the prism of a global world order. Foreign and domestic studies and researchesof the Ukrainian geopolitical crises are generalized in the article. Vision of the formation of moderngeopolitical status of Ukraine, same as probable ways of it’s development, is based on the analysis ofthe foreign policy priorities in the president and parliamentary preelection programmes. The nextconclusion is substantiated: Ukraine is an important geopolitical center, but it is not an active orvivid participant of international relations.